APXS‐derived chemistry of the Bagnold dune sands: Comparisons with Gale Crater soils and the global Martian average. Issue 12 (12th December 2017) - O'Connell‐Cooper, C. D.; Spray, J. G.; Thompson, L. M.; Gellert, R.; Berger, J. A.; Boyd, N. I.; Desouza, E. D.; Perrett, G. M.; Schmidt, M.; VanBommel, S. J.
Abstract: We present Alpha‐Particle X‐ray Spectrometer (APXS) data for the active Bagnold dune field within the Gale impact crater (Mars Science Laboratory (MSL) mission). We derive an APXS‐based average basaltic soil (ABS) composition for Mars based on past and recent data from the MSL and Mars Exploration Rover (MER) missions. This represents an update to the Taylor and McLennan (2009) average Martian soil and facilitates comparison across Martian data sets. The active Bagnold dune field is compositionally distinct from the ABS, with elevated Mg, Ni, and Fe, suggesting mafic mineral enrichment and uniformly low levels of S, Cl, and Zn, indicating only a minimal dust component. A relationship between decreasing grain size and increasing felsic content is revealed. The Bagnold sands possess the lowest S/Cl of all Martian unconsolidated materials. Gale soils exhibit relatively uniform major element compositions, similar to Meridiani Planum and Gusev Crater basaltic soils (MER missions). However, they show minor enrichments in K, Cr, Mn, and Fe, which may signify a local contribution. The lithified eolian Stimson Formation within the Gale impact crater is compositionally similar to the ABS and Bagnold sands, which provide a modern analogue for these ancient eolian deposits. Compilation of APXS‐derived soil data reveals a generally homogenous global composition for Martian soils but one that can be locally modified due to past or extant geologic processes that are limited in both space and time. Key Points: Gale soils are compositionally similar to a global basaltic Martian soil but with slight evidence of local contribution The sands of the Bagnold barchan dunes are compositionally distinct with mafic enrichment The active Bagnold sands are low in dust as evidenced by low S, Cl, and Zn concentrations